Is the PowerCal device suitable for monitoring performance with competitive cyclists? - Paton, C. D.; Costa V. P. (Journal of Science and Cycling, 2017)
The use of bicycle power meters is becoming an increasingly popular, although somewhat costly, means of monitoring training adaptations in competitive cyclists. The PowerCal (PCal) is a low-cost power prediction device that may offer an alternative means of monitoring cycling performance. The aim of this study was to determine the validity and reliability of the PCal in comparison to a laboratory standard ergometer, over a range of constant load powers. Nine trained male cyclists (35±9yrs, 177±5cm, 74±6kg) completed two exercise trials on a Velotron ergometer (VTron) while wearing the PowerCal (PCal) device. During each trial participant`s performed six constant-load efforts commencing at 100W and increasing by 40W increments up to a final exercise intensity of 300W. Power output predicted by the PCal was significantly lower (p<0.05) than that measured by the VTron in all but the 100W load condition. The group mean bias (± 95%CL) in the PCal prediction across all loads was -19.3% ± 5.3% while individual subject bias covered a wide range from -41.2% to +6.6%. Correlations between each individuals predicted and measured power were all significant (r =0.93). There were no significant differences (p>0.05) in predicted power at any workload between repeat trials. The mean re-test typical error was similar (~6W) across all measured power outputs, corresponding to a mean coefficient of variation of ~5% between trials. The PCal reports substantially lower power outputs compared to the VTron ergometer. Furthermore the variability in the PCal measures across repeated trials of ~5% makes it unsuitable for monitoring performance changes that maybe considered worthwhile in trained competitive cyclists.